Training Effectiveness in Change Knowledge and Attitude of Social Health Workers (Cadres) on Tuberculosis Disease - Diah Prasetyorini; Hari Kusnanto; Mora Claramita (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2019)
Background: Tuberculosis is a contagious disease that is still a public health problem. Indonesia is the country with the second most frequent tuberculosis cases in the world. One of the element that play a role in tuberculosis control is qualified human resources, including health cadres.Objectives: To determine the effectiveness of training to increase knowledge and change the attitude of the health cadres against tuberculosis in Gunungkidul.Methods: This study uses the Quasy Experiment research design, with a pretest-posttest design. Before the given intervention is given a pretest, then intervention in the form of training, after that do the posttest. After that analysis and test significance.Results: There were 70 health cadres, 35 were given intervention (training) and 35 as controls. There was a significant increase in knowledge in training cadres (p < 0.05) and there was a difference in the level of knowledge between trained and untrained (p < 0.05), there was a change in attitude on the trained and untrained cadres (p < 0.05).Conclusions: With the training, it can be improve knowledge and influence the attitude of health cadres against tuberculosis.